Frenemies: feminists, conservatives, and sexual violence - Whittier, Nancy (Oxford University Press, 2018)
What happens when enemies work to advance similar goals? Who wins, who loses, and why? In Frenemies, Nancy Whittier addresses this question through a study of feminist and conservative opposition to pornography, campaigns against child sexual abuse, and engagement on the Violence Against Women Act. Drawing on extensive research, Whittier shows how feminist and conservative activists interacted with each other and with the federal government, how their interaction affected them, and what each side achieved. Whittier re-conceptualizes relationships between social movements, presenting a model of how "frenemies"--groups that are neither allies nor opponents--work toward related goals. She outlines the dynamics and paths of frenemy relationships, describing the unintended consequences for the groups involved and for their respective movements at large. With high levels of political polarization across the U.S., Frenemies provides a crucial look at both the promise and the risk of cooperation across political differences. -- !c From back cover